Donald Morote-Revolledo MD - Morales Landeo, Edgar (2018)
An illustrious Arequipa citizen, Donald Morote-Revolledo MD was born in 1928. He was an innate leader and a multi-talented academician, his activities involved teaching, healthcare and politics. He was a pioneer of vascular neurosurgery in Peru. Being a quite sensitive person and always helpful for those in need, he organized a group of professionals for delivering emergency medical care to people affected by Huaraz earthquake in 1970, where more than 70,000 thousand people died. Master and trainer of several promotions of several promotion of medical residents, it is through this historical tribute to him.